Immune responses to human papillomavirus infection and vaccination - Kiamba, Eunice Wavinya; Goodier, Martin R.; Clarke, Ed (Frontiers in Immunology, 2025)
Human papillomavirus (HPV) is the most common sexually transmitted infection. About 90% of HPV infections are transient, resolving without any need for intervention. Most of HPV infections are low-risk non-oncogenic. However, persistent infection with high-risk oncogenic HPV types is the cause of cervical as well as various other anogenital and oropharyngeal cancers. HPV infection on either cutaneous or mucosal surfaces activates both innate and adaptive antiviral immune cells including Langerhans and keratinocyte cells, natural killer cells, B and T cells. These cellular responses alongside their corresponding cytokine profiles have been associated with clearance of HPV infection and regression of HPV associated disease although the actual immune mechanisms involved are not well understood. Current HPV vaccines are based on self -assembled virus-like particles (VLP) from the major viral capsid protein and target the high-risk HPV types as well as two low-risk types responsible for genital warts. The vaccines generate antibody protection against new infections with no effect on already established infections and HPV-associated diseases. Certainly, despite the high effectiveness of current prophylactic HPV vaccines, therapeutic HPV vaccines are needed for treatment of already established HPV infections and disease. Although there have been great efforts in development of therapeutic vaccines, none is yet to be licensed due to low efficacy and safety concerns. There is therefore a need to understand both natural and vaccine-induced immunity, for development of effective and safe therapeutic HPV vaccines. Additionally, a better understanding of the immunogenicity of HPV vaccines, which are among the best subunit vaccines developed to date, may identify immune pathways that could be targeted for development of similarly effective vaccines for other diseases. This review summarises available literature on immune responses to both HPV infection and vaccination, with an aim of improving overall understanding on this subject. This may provide insights for better targeting of both therapeutic and prophylactic vaccines, not only for HPV but also other antigen targets.